Relationship between labour force satisfaction, wages and retention within the UK National Health Service: a systematic review of the literature. Issue 7 (21st July 2020) - Bimpong, Kweku Andrew Ampadu; Khan, Ausaf; Slight, Robert; Tolley, Clare L; Slight, Sarah P
Abstract : Objectives: A systematic review was undertaken to understand the nature of the relationship between the UK National Health Service (NHS) labour force and satisfaction, retention and wages. Design: Narrative systematic review. Data sources: The literature was searched using seven databases in January 2020: MEDLINE (1996–present), the Cumulative Index to Nursing and Allied Health Literature (CINAHL via EBSCO) (1984–present), Embase (1996–present), PsycINFO (1987–present), ProQuest (1996–present), Scopus (all years) and Cochrane library (all years). We used medical subject headings and key words relating to 'retention', 'satisfaction' and 'wages'. Eligibility criteria for selecting studies: Primary research studies or reviews that focused on the following relationships within the NHS workforce: wages and job satisfaction, job satisfaction and retention or wages and retention. Data extraction and synthesis: Two independent reviewers screened all titles, abstracts and full texts, with arbitration by a third reviewer. Results: 27 803 articles were identified and after removing duplicates (n=17 156), articles were removed at the title (n=10 421), abstract (n=150) and full-text (n=45) stages. A total of 31 full-text articles were included. They identified three broad themes, low job satisfaction impacting negatively on job retention, poor pay impacting negatively on staff satisfaction and the limitations of increasing pay as a means of improving staff retention. Several factors affected these relationships, including the environment, discrimination, flexibility, autonomy, training and staffing levels. Conclusions: This review highlighted how multiple factors influence NHS labour force retention. Pay was found to influence satisfaction, which in turn affected retention. An increase in wages alone is unlikely to be sufficient to ameliorate the concerns of NHS workers. More research is needed to identify the role of autonomy on retention. A system leadership approach underpinned by data is required to implement bespoke job satisfaction improvement strategies to improve retention and achieve the goals of the NHS Long Term Plan.